Management of Gamified Lesson: Understanding Aesthetics and Acceptance among Learners - Nor Azairiah Fatimah Othman; Amir Imran Zainoddin; Azila Jaini; Mazida Ismail; Siti Fatimah Mohamad Radzi; dan Norashikin Hussein (Information Management and Business Review, 2023)
Joyful learning evokes happy feelings and subsequently induces positive academic achievement.  With the rise of mental health issues due to intense study among students, gamification has recently grown in popularity among academic institutions to make learners happier, more engaged and ultimately improve learning outcomes. However, the management of gamified lessons has been a problem for years for all education levels on a varying basis. Nowadays, it is increasingly recognized that not all learners are acceptive of gamified lessons for learning. Drawing on a survey of 283 students of higher learning institutions, this study found that aesthetics, perceived ease of use, perceived usefulness and perceived enjoyment have a favorable impact on the intention to accept gamification in learning among learners. This study contributes to under-investigated scholarly works of suitable conditions under which gamified lesson best takes place with regard to aesthetics and learners’ acceptance that would be beneficial for the effective management of gamification.